Evaluasi Kinerja Pegawai Dinas Kesehatan Kota Surabaya: Tinjauan dari Aspek Motivasi, Disiplin, dan Lingkungan Kerja - Sutopo Sutopo (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Employee performance may be a critical criterion in determining a government institution's success during the era of increasingly active open service transformation.This study uses a quantitative approach and a straightforward, illustrative methodology to investigate employment.Validity Test: KMO-MSA 0.847 (qualified 0.5), Bartlett's Test crucial (p 0.05), and stacking compute esteem of 0.5 for all explanation items Unwavering quality test, representative execution (α 0.894), work environment (α 0.883), work inspiration (α 0.892), and work teaching (α 0.875) The comes about of measurable investigation appeared that work inspiration had a positive and noteworthy impact on the execution of representatives of the Surabaya City Wellbeing Office with a way coefficient of 0.486 (p 0.05). With a track coefficient of 0.534 (p 0.05), the results of the speculation test show that work instruction has a significant and favorable influence on representational execution. The work environment has a significant and favorable effect on employee performance, as evidenced by a track coefficient of 0.428 (p 0.05). With an R2 of 0.724, the auxiliary demonstrate test suggests that work environment, work inspiration, and work instruction all simultaneously affect worker execution.